Hydro-Grain-Texture Modeling of Systematics of Propagation, Branching, and Coalescence of Fluid-Driven Fractures - Wang, Suifeng; Elsworth, Derek; Zhang, Liping; Zhao, Xianyu; Wang, Tao (Rock mechanics and rock engineering, 2025)
The heterogeneity of the mineral grain structure and presence of pre-existing flaws significantly impacts fracture propagation within amorphous crystalline rocks. We explore the macro-mechanical response derived from microfracture evolution for fluid-driven fracturing (hydraulic fracturing) in a granite with pre-existing flaws. We introduce a hydro-grain-texture model (HGTM) based on a “grain growth” algorithm that accurately characterizes the microscale granular structure of minerals subject to the influence of driven fluids. The single and double flaws of different geometries are introduced to investigate hydraulic fracture propagation in granites under combined influence of heterogeneity and anisotropy. The results demonstrate that the HGTM can consistently reproduce the principal features of fracture propagation and coalescence observed in experiments. It is found that the hydraulic fracturing results (fracture number, type, and tortuosity) and breakdown pressure are affected by the interactions of confining stress, mineral heterogeneity, and flaw geometry. Confining stress induces the extension of fluid-driven fractures in the direction of the maximum principal stress. While with absence of confining stress, fractures tend to extend along the long axis of the flaw and are more susceptible to grain boundaries and breakdown pressure is also primarily determined by the local strength at the flaw tip. In double flaw specimens, both the flaw bridging angles and confining stress jointly influence the patterns of fracture propagation and coalescence.HighlightsA novel hydro-grain-texture model (HGTM) is proposed to investigate the hydraulic fracturing behavior of crystalline rock.The combined influence of mineral heterogeneity, confining stress condition, and flaw geometry on hydraulic fracturing is investigated.Fluid-driven fracturing propagation, branching, and coalescence in granite containing single and double flaws are reproduced.The fracture tensile failure mode mechanism in hydraulic fracturing test is investigated.